(untitled) (Research, Society and Development, 2020)
This work aims to evaluate the acute toxicity in vivo of the extract of B. genistelloides orally in murine models, as well as to analyze the quality of these samples sold in fairs sold outdoors, as well as in herbs. The samples for the study came from the establishments mentioned above, located in the municipality of Campina Grande, in Paraíba. Such samples were subjected to tests in order to verify quality control, such as foreign material, humidity, pH, acid insoluble ash and also total ash and toxicological tests in murine models with administration of the crude extract orally. When the parameter established by the quality control was verified, it was possible to identify that the value of the samples from Feira Livre 2 and also from the herbalist were found to be above the standard value when analyzing the material not from the original product, however, in the phytochemical prospecting result for the presence of flavonoids, saponins and tannins had a positive response. In acute toxicity in animals, the extract was not toxic and obtained an LD50 of 5000 mg / kg, whereas for Artemia salina in doses of 2 to 10 mg / ml, this was toxic. When the macroscopic and statistical evaluation of the organs of the animals was performed, they did not present any changes. The gorse showed a diuretic effect on the animals during the 14 days of the experiment. When the samples are analyzed, the conditioning and labeling factor leaves something to be desired, since the packaging must contain at least the scientific and popular name of the plant.